Isolasi Bakteri Pendegradasi Minyak Dari Perairan Sekitar Pelabuhan Bengkalis Provinsi Riau - Andhini, Nadia; Nursyirwani, Nursyirwani; Nedi, Syahril (Jurnal Perikanan dan Kelautan, 2018)
Oil degradation bacteria can be found in various habitats in the marine environment including in the waters around the harbor. This study aims to isolate the oil degrading bacteria from waters around the port of Bengkalis and test its ability to degrade crude oil. Isolation of the degrading bacteria has been done from February to April 2017 at the Marine Microbiology Laboratory, Department of Marine Science, Faculty of Fish-eries and Marine University of Riau. The amount of oil degrading bacteria ranges from 0.2 x 105 to 8.9 x 105 CFU/ml. The isolation result was obtained by 10 isolates of oil degradation bacteria, ie BM1a, BM1b, BM1c, BM1d, BM7a, BM7b, BM7c, BM7d, BM14a and BM14b. Identification based on morphological, physiological and bio-chemical characteristics of each isolate, all isolates were round and elevated, six were white in color, three were yellow, one cream-colored isolate, eight isolates with slip-pery edges and two isolates with periphery waves, seven isolates were indol positive, two isolates produced H2S, four isolates were methyl red positive, all isolates were motile, capable of fermentation of glucose and sucrose in sugar test, able to ferment citrate, positive catalase and Gram negative bacteria. For degradation test only five bacterial isolates were selected of BM1a, BM1b, BM1c, BM7a and BM7d. The highest degradation at 1% concentration was indicated by isolate BM1a, the highest degrada-tion at 2% and 3% concentrations was indicated by BM1c isolate. Therefor, bacteria isolate capable of degrading the highest crude oil was BM1c.